• Matéria: Matemática
  • Autor: ruthbmeloo
  • Perguntado 7 anos atrás

3×-5 (×-2) = (3×-1) 2​


leonardotoledosan: 3x-5x+10=6x-2 → -8x+8=0 → -8x=-8 (-1) → x=1

Respostas

respondido por: Kakaw28
0

Resposta:

Explicação passo-a-passo:

3X-5 (X-2) = (3X-1).2\\ (fazendo a distributiva)

3x^{2} -5X+12=0

respondido por: mgs45
0

3x - 5 (x-2) = (3x-1)2

3x - 5x + 10 = 6x - 2

3x - 5x - 6x = -2 - 10

-8x = - 12

x = \frac{-12}{-8}

x = \frac{-12 : 4}{-8 : 4}

x = \frac{3}{2}

Anexos:
Perguntas similares